2020
DOI: 10.1037/abn0000639
|View full text |Cite
|
Sign up to set email alerts
|

Reduced positive affect on days with stress exposure predicts depression, anxiety disorders, and low trait positive affect 7 years later.

Abstract: Positive emotions serve important functions for mental health. Susceptibility to reduced positive emotions in the context of stress may increase risk for poor mental health outcomes, including anxiety and depressive disorders and low overall levels of positive emotion. In an 8-day daily diary study within a larger panel study (N = 1,517), we tested whether degree of reduction in time spent experiencing positive affect on days of stress exposure predicted lower levels of positive affect and elevated risk for ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…Positive emotions have been shown to have an important function for mental health, with reduced positive emotions in the context of stress increasing the risk of poor mental health outcomes [7]. Mentoring and supervision, in encouraging self-direction in research, have been identified as unsurpassed in their ability to positively affect graduate students to increase their work satisfaction and fulfilment [8].…”
Section: Introductionmentioning
confidence: 99%
“…Positive emotions have been shown to have an important function for mental health, with reduced positive emotions in the context of stress increasing the risk of poor mental health outcomes [7]. Mentoring and supervision, in encouraging self-direction in research, have been identified as unsurpassed in their ability to positively affect graduate students to increase their work satisfaction and fulfilment [8].…”
Section: Introductionmentioning
confidence: 99%
“…These patterns are also found when BIS hypersensitivity is measured directly (Gray, 1987;Leen-Feldner et al, 2004;Tull et al, 2010), especially at times of actively stressful situations (Heponiemi et al, 2003;Rackoff & Newman, 2020). On the other hand, higher levels of BAS sensitivity and extraversion predict a greater preference for most positive emotions (Khazanov et al, 2020), along with coping styles that pursue such emotions, such as positive reappraisal (Barańczuk, 2019;Carl et al, 2013;Gable et al, 2000).…”
mentioning
confidence: 74%
“…This demonstrates how the direct impacts of COVID-19 on life situations (e.g., loss of close others, changes in employment, financial situations and relationships) can meaningfully impacting mental health among the population. These risk factors of poor mental health were seen in evidence from both before-(23, 24) and during-COVID-19. (4) These results firstly suggest that the demand for mental healthcare might increase further post-restrictions, posing challenges for psychiatry and primary care.…”
Section: Discussionmentioning
confidence: 97%